Resilience of Zostera muelleri seagrass to small‐scale disturbances: the relative importance of asexual versus sexual recovery. Issue 4 (21st January 2014) - Macreadie, Peter I.; York, Paul H.; Sherman, Craig D.H.
Abstract Resilience is the ability of an ecosystem to recover from disturbance without loss of essential function. Seagrass ecosystems are key marine and estuarine habitats that are under threat from a variety of natural and anthropogenic disturbances. The ability of these ecosystems to recovery from disturbance will to a large extent depend on the internsity and scale of the disturbance, and the relative importance of sexual versus asexual reproduction within populations. Here, we investigated the resilience of Zostera muelleri seagrass (Syn. Zostera capricorni) to small‐scale disturbances at four locations in Lake Macquarie – Australia's largest coastal lake – and monitored recovery over a 65‐week period. Resilience of Z. muelleri varied significantly with disturbance intensity; Z. muelleri recovered rapidly (within 2 weeks) from low‐intensity disturbance (shoot loss), and rates of recovery appeared related to initial shoot length. Recovery via rhizome encroachment (asexual regeneration) from high‐intensity disturbance (loss of entire plant) varied among locations, ranging from 18‐35 weeks, whereas the ability to recover was apparently lost (at least within the time frame of this study) when recovery depended on sexual regeneration, suggesting that seeds do not provide a mechanism of recovery against intense small‐scale disturbances. The lack of sexual recruits into disturbed sites is surprising as our initial surveys of genotypic diversity (using nine polymorphic microsatellite loci) at these location indicate that populations are maintained by a mix of sexual and asexual reproduction (genotypic diversity [R] varied from 0.24 to 0.44), and populations consisted of a mosaic of genotypes with on average 3.6 unique multilocus genotypes per 300 mm diameter plot. We therefore conclude that Z. muelleri populations within Lake Macquarie rely on clonal growth to recover from small‐scale disturbances and that ongoing sexual recruitment by seeds into established seagrass beds (as opposed to bare areas arising from disturbance) must be the mechanism responsible for maintaining the observed mixed genetic composition of Z. muelleri seagrass meadows.